Procedural assessments of SOPs to ensure SOPs are logical and meet GXP requirements - Ollier, Susan; Wilson, Pam (Henry Stewart Talks, 2013)
Procedural assessment cycle and tools of SOPs, Working instruction template, The SOP title, The scope of content, When scope covers multiple tasks or is a part of a larger process, Filling the scope, procedure & checklist in our template, Authors, general requirements and further elements of content, Importance of up-to-date information, Proper writing & revising of the content, Preparing a checklist, Regulatory requirements, Sources of information, Documentation, Format and language, Points to remember, Added value – Feasibility